De la formación integral universitaria a la construcción de gobernabilidad (2016)
This article aims to aims to have an engagement with the university dynamics and identify not only its academic function but also its concern in the construction of society. It hopes to achieve this through the settings of reflection, analysis and debate, which are provided, created and consolidated by the same university so that university students, throughout their process of learning and as people that bear their own principles, think in a new society, and contribute in the same way to the construction of governance.This reflection was born out of the investigative process that has come as a result of the work in Ethics, Mankind and Society of the “Humanist Expeditionaries” group, in which the topic of interest has focused on describing the political dynamics of young people in the academic and political setting, given that their process of learning aims to recognize the human, ethical and social side of things, allowing the student to come to a closer understanding of the reality which affects them, as the university aims to con- tribute to social problems as part of its principles, through the integrated education of its students. As a reflection of this ideal that the university pursues and which it should continue to pursue continuously, the need arises to think in the process that should be followed in terms of integrated education, in order to contribute to the construction of governance in contemporary Colombia.